Impact of prior oral anticoagulation on admission stroke severity in patients with atrial fibrillation - Franc, David; Sanak, Daniel; Kral, Michal; Hutyra, Martin; Taborsky, Milos; Divisova, Petra; Zapletalova, Jana (Biomedical papers, 2024)
Background and Aims. In patients with atrial fibrillation, oral anticoagulation therapy is indicated for both primary and secondary prevention of stroke/systemic embolism. Though direct oral anticoagulants with greater safety and efficacy than warfarin were introduced into clinical practice at the beginning of the last decade, even now not all patients with AF have adequate preventative anticoagulant treatment. The primary goal of this study was to evaluate the impact of prior use of oral anticoagulants on admission stroke severity in those with AF. Other aims were, inter alia, to assess the trend in atrial fibrillation prevalence in the years of the HISTORY trials 2012-2021 carried out in the Czech Republic and use of oral anticoagulants (OAC) in ischemic stroke (IS) patients.Methods. We analyzed consecutive ischemic stroke patients who had been enrolled in the HISTORY (Heart and Ischemic STrOke Relationship studY) study registered on ClinicalTrials.gov (identifier NCT01541163) in the year 2012 and carried out a yearly comparison (detailed in the text).Results. In total, there were 1059 patients (55.9% males, mean age 71.7 extpm12.8). There was no significant difference over the time period in rate of known (18.3 vs. 16.5%, P=0.442) or newly detected AF (17.0 vs. 16.0%, P=0.665), but sigificantly more patients with known AF were treated with oral anticoagulants before IS in the year 2021 (32.1 vs. 70.7%, P<0.0001), and direct oral anticoagulants (3.6 vs. 35.4%, P<0.0001). The number of patients with atrial fibrillation had not changed significantly over the years (26.2 vs. 31.3%). Patients on OAC had a lower median admission score on the National Institutes of Health Stroke Scale (NIHSS) than those not using an oral anticoagulant (6 vs. 16, P=0.0004) in 2021.Conclusions. There was no significant upward trend in atrial fibrillation in stroke patients admitted between 2012 and 2021, but patients with known AF were significantly more frequently treated with oral anticoagulants and direct oral anticoagulants (DOAC) in 2021. Patients on OAC had lower admission NIHSS scores than those not using any anticoagulent in the year 2021. The difference in the median admission NIHSS between the patients on OAC and those without OAC treatment was not significant in the year 2012 (6 vs. 12, P=0.066). This might be related to the fact that substantially fewer patients in 2012 were on DOACs, which are considered more effective than warfarin.
Keywords: ischemic stroke; atrial fibrillation; oral anticoagulation; direct oral anticoagulants; stroke severity